#### Answer

True.

#### Work Step by Step

It's true that $(-a)^n=-a^n$ if $n$ is odd and $a$ is a positive integer because:
$(-a)^n=(-1*a)^n=(-1)^n(a)^n=-1a^n=-a^n$
(we know that $(-1)^n=-1$ if $n$ is odd.)

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

True.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.